A comparative analysis of the different damage of retina after eye injury in children (Ukrainian Journal of Ophthalmology, 2026)
Introduction. Eye injury in children involving the retina is the most difficult to treatment and recovery of vision function.Aim. To study the frequency of retinal damage, regularities and prognostic factors predicted the functional outcome (visual acuity) after injuries of the eyeball in children.Material and Methods. Medical records of 91 consecutive patients after eye injury in children involving the posterior segment were analyzed. All patients were hospitalize in Kiev Eye Microsurgery Centre, Kiev in period 2009—2011. Results. The injuries diagnosed with damage to the retina was 91 of these, 57 (62.6 %) were accomplish by retinal detachment. The causes of retinal detachment were — retinal dialysis, 30 (33 %), the one tear 18 (19.8 %), a giant tear 4 (4.3 %), laceration/ impact site 4 (4.4 %), contusion retinopathy 1 (1.1 %). The macula was involved in the process of detachment in 37 (65 %) patients. Conclusions. The main causes of low visual acuity after retinal detachment in our study were macula involvement before surgery (p
Keywords: eye injury; retinal detachment; macula; proliferative vitreoretinopathy